2012
DOI: 10.1103/physrevb.86.184433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetization pinning on the spectrum of spin waves in magnonic antidot waveguides

Abstract: We study the spin-wave spectra in magnonic antidot waveguides (MAWs) for two limiting cases (strong and negligible) of the surface anisotropy at the ferromagnet/air interface. The MAWs under investigation have the form of a thin stripe of permalloy with a single row of periodically arranged antidots in the middle. The introduction of a magnetization pinning at the edges of the permalloy stripe and the edges of antidots is found to modify the spin-wave spectrum. This effect is shown to be necessary for magnonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 43 publications
(22 reference statements)
1
40
0
Order By: Relevance
“…The origins of these two bandgaps were found to be different. The first one opens at the BZ boundary due to the Bragg reflection of SWs, while the second gap opens up within the BZ38. It was shown that this splitting of the bands within the BZ is due to the anti-crossing between two families of modes34, those with and without a nodal line in the upper and lower parts of the ADLW (see the first row of profiles in the bottom panel of Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The origins of these two bandgaps were found to be different. The first one opens at the BZ boundary due to the Bragg reflection of SWs, while the second gap opens up within the BZ38. It was shown that this splitting of the bands within the BZ is due to the anti-crossing between two families of modes34, those with and without a nodal line in the upper and lower parts of the ADLW (see the first row of profiles in the bottom panel of Fig.…”
Section: Resultsmentioning
confidence: 96%
“…We showed in Ref. 38 that the pinning at the edges of Py (at the waveguide edges and at edges of antidots) is crucial for the existence of these magnonic gaps.…”
Section: Resultsmentioning
confidence: 99%
“…We did not include bulk magnetocrystalline anisotropy in considered model but the plane wave method, used in our calculations, introduces magnetization pinning on the interfaces between magnetic and non-magnetic material which can be equivalent to the presence of the surface anisotropy. 71 We are going to consider the system with relatively thick layers (in the range of few lm). The collective spin wave dynamics in the PMC is due to magnetostatic interaction, because the non-magnetic layers prevent an exchange coupling between magnetic slabs.…”
Section: Structurementioning
confidence: 99%
“…[30][31][32][33][34][35] Magnonic antidot waveguide (MAW) is an attractive option for manipulation of transmitted spin waves towards the above application, but it has only recently been started to be explored. [36][37][38] So far, a study of the dependence of spinwave dispersion on the shapes of the antidots has not been reported. More importantly, how changes in the exchange field distribution around the antidot boundary can alter the characteristic dispersion of exchange or dipole-exchange SWs in a MAW, has never been observed before.…”
Section: Magnonicsmentioning
confidence: 99%